2022
DOI: 10.3390/jcm11010274
|View full text |Cite
|
Sign up to set email alerts
|

Association between CHADS2, CHA2DS2-VASc, ATRIA, and Essen Stroke Risk Scores and Unsuccessful Recanalization after Endovascular Thrombectomy in Acute Ischemic Stroke Patients

Abstract: Background: The CHADS2, CHA2DS2-VASc, ATRIA, and Essen scores have been developed for predicting vascular outcomes in stroke patients. We investigated the association between these stroke risk scores and unsuccessful recanalization after endovascular thrombectomy (EVT). Methods: From the nationwide multicenter registry (Selection Criteria in Endovascular Thrombectomy and Thrombolytic therapy (SECRET)) (Clinicaltrials.gov NCT02964052), we consecutively included 501 patients who underwent EVT. We identified pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Successful recanalization is more likely to influence functional outcomes than other factors that contribute to the stroke risk score. We previously reported that the CHADS 2 , CHA 2 DS 2 -VASc, ATRIA, and Essen scores could be used to predict recanalization in stroke patients receiving EVT [ 19 ]. We explored associations between stroke risk scores and functional outcomes at 3 months and found a positive association between all stroke risk scores and unfavorable outcomes after adjusting for covariates that could be identified before the procedure, whereas there was a positive association between CHADS 2 and ATRIA scores and unfavorable outcomes in multivariable regression analysis after covariate adjustment, including successful recanalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful recanalization is more likely to influence functional outcomes than other factors that contribute to the stroke risk score. We previously reported that the CHADS 2 , CHA 2 DS 2 -VASc, ATRIA, and Essen scores could be used to predict recanalization in stroke patients receiving EVT [ 19 ]. We explored associations between stroke risk scores and functional outcomes at 3 months and found a positive association between all stroke risk scores and unfavorable outcomes after adjusting for covariates that could be identified before the procedure, whereas there was a positive association between CHADS 2 and ATRIA scores and unfavorable outcomes in multivariable regression analysis after covariate adjustment, including successful recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…All patient information was anonymized and audited by the main center. Demographic data, comorbidities, including vascular risk factors, medication history, and laboratory results, neurologic status, including severity and functional outcomes, variables of reperfusion therapy (time parameters for tPA and EVT, techniques, devices, and treatment-related complications), and imaging findings before and after reperfusion therapy were collected for all patients [ 19 , 23 ]. The SECRET study was conducted according to the guidelines of the Declaration of Helsinki and approved by the Institutional Review Board of the Yonsei University College of Medicine (4-2015-1196).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous thrombolysis is the standard resuscitation measure to minimize brain damage. , Although thrombolytic therapy is strictly time-limited, timely thrombolysis can be effective in relieving neurological damage. , The recombinant fibrinogen activator rtPA is the only effective thrombolytic agent approved by the FDA for clinical use in acute IS. , However, because of the short therapeutic window suitable for most patients (≤4.5 h), with the development of new thrombolytic agents and advanced imaging techniques that allow longer thrombolysis times based on advanced imaging, the concept of tissue time window has been proposed and the treatment time window has been extended to 6 h . Among other limitations, the therapeutic effect of rtPA is often unsatisfactory. , Additionally, a high risk of reperfusion injury and cerebral hemorrhage remain after thrombolysis . Mechanical thrombectomy is also used clinically to treat IS.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, because of the short therapeutic window suitable for most patients (≤4.5 h), with the development of new thrombolytic agents and advanced imaging techniques that allow longer thrombolysis times based on advanced imaging, the concept of tissue time window has been proposed and the treatment time window has been extended to 6 h. 13 Among other limitations, 14 the therapeutic effect of rtPA is often unsatisfactory. 12,15 Additionally, a high risk of reperfusion injury and cerebral hemorrhage remain after thrombolysis. 16 Mechanical thrombectomy is also used clinically to treat IS.…”
Section: Introductionmentioning
confidence: 99%